Alterations of Fungal Microbiota in Patients With Cholecystectomy - Xu, Jun; Ren, Xinhua; Liu, Yun; Zhang, Yuanyuan; Zhang, Yiwen; Chen, Guodong; Huang, Qing; Liu, Qing; Zhou, Jianhua; Liu, Yulan (Frontiers in Microbiology, 2022)
Increasing evidence suggests a high risk of gastrointestinal post-operative comorbidities (such as colorectal cancer) in post-cholecystectomy (PC) patients. Although previous studies implicated the role of fungi in colon carcinogenesis, few reports focused on the fungal profile in PC patients. We enrolled 104 subjects, including 52 PC patients and 52 non-PC controls (CON), for fecal collection to detect the fungal composition by internal transcribed spacer (ITS) V1 rDNA sequencing. Data showed the Candida (C.) glabrata and Aspergillus (A.) Unassigned were enriched, and C. albicans was depleted in PC patients. In addition, postoperative duration was the main factor to affect the fungal composition. Machine learning identified the C. glabrata, A. Unassigned, and C. albicans were three biomarkers to discriminate PC patients from CON subjects. To investigate the fungal role in colon carcinogenesis, the subjects of the PC group were divided into two subgroups, including PC patients without (nonCA) and with precancerous lesions or colorectal cancer (preCA_CRC), by histopathological evidences. C. glabrata was found to be gradually accumulated in different statuses of PC patients. In conclusion, we found a fungal dysbiosis in patients with cholecystectomy, and the postoperative duration was a potent factor to influence the fungal composition. The accumulation of C. glabrata might be connected with carcinogenesis after cholecystectomy.